Reliable Algorithm of Homotopy Analysis Method for Solving System of Integral Equations - Mohammed, Osama H; Khaleel, Omar I (Al-Nahrain Journal of Science, 2018)
This paper presents an approximate solution for systems of Volttera integral equations of the second kind using a reliable algorithm of homotopy analysis method. The solution is calculated in the form of convergent series with easily compatible components. The approach is tested for some examples and the results demonstrate reliability and efficiency of the proposed method